KEDISIPLINAN PEGAWAI DALAM MENINGKATKAN HASIL KERJA PADA MASA PANDEMI COVID – 19 - Putra, Rusman Pratama; Razak, Andi Rosdianti; Parawangi, Anwar (Universitas Muhammadiyah Makassar, 2023)
This study aims to find out how the performance of Somba Opu District employees in providing population administration services to the community. This research is a qualitative research using descriptive methods with an inductive approach. The technique for collecting data is by using interviews, observation and documentation. Based on the results of research and data processing, it can be concluded that the performance of employees in providing services to the community in Somba Opu District, Gowa Regency, South Sulawesi Province is quite good but not optimal because there are still problems in its implementation, namely in the quantity of work indicators, this is due to facilities that are already feasible to be renewed such as computers and networks that often have errors, indicators of community satisfaction related to people who do not understand service procedures, as well as problems related to staff shortages.